(untitled) (Fiep Bulletin - online, 2015)
The aims of the present study were to evaluate the anaerobic power of athletes of the elite of synchronized swimmers (17.0 ±1,4 year) and a group of non-athletes (21.0 ±2, 6.0 years) by the Wingate test (30 s). The adopted load was of 0.075 kg for kilogram of corporal weight. The analyzed parameters had been: the fatigue index, power prick and the average power. The group of senior athlete presents greater anaerobic capacity than the junior athlete.